NASOSNI BURCHAK TEZLIGI O‘ZGARISHIDA ISHCHI PARAMETRLARNI НISOBLASH - Uzaqov , Navruz Choriyor o‘g‘li; Radjabov, Shaxboz Baxtiyor o‘g‘li (Innovative Development in Educational Activities, 2023)
To date, significant progress has been made in the application of contour blasting when cutting ledges in quarries. However, a number of key issues on the forecast assessment and selection of a rational technology for cutting ledges, as well as improving the parameters of borehole explosive charges during contour blasting, have not been resolved. At the same time, when choosing the parameters of drilling and blasting operations, the requirements of the stability of the sides of quarries are not sufficiently taken into account. In this regard, there is a need to carry out scientific research on the development of methods for managing the stability of the sides of quarries, taking into account the technology of conducting BWR, improving the parameters of contour blasting and obtaining steeper and more stable slopes of ledges on the limit contour of the quarry to ensure the safety of the legal massif, the safety of mining operations and reducing the volume of overburden work.